Performance and combustion characteristics of a DI diesel engine fueled with waste palm oil and canola oil methyl esters - SAYIN, CENK (ELSEVIER SCI LTD, 2009)
This study discusses the performance and combustion characteristics of a direct injection (DI) diesel engine fueled with biodiesels such as waste (frying) palm oil methyl ester (WPOME) and canola oil methyl ester (COME). In order to determine the performance and combustion characteristics, the experiments were conducted at the constant engine speed mode (1500 rpm) under the full load condition of the engine. The results indicated that when the test engine was fueled with WPOME or COME, the engine performance slightly weakened; the combustion characteristics slightly changed when compared to petroleum based diesel fuel (PBDF). The biodiesels caused reductions in carbon monoxide (CO), unburned hydrocarbon (HC) emissions and smoke opacity, but they caused to increases in nitrogen oxides (NOx) emissions. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Alternative fuel; Cylinder gas pressure; Injection line pressure; Heat release; Emissions; EXHAUST EMISSIONS; VEGETABLE-OILS; BIODIESEL FUEL; INJECTION; PRESSURE; BLENDS